Implicit Negation in Dialogue Discourse - Sitdikova, Farida Bizyanovna; Eremeyeva, Guzel Rinatovna; Valieva, Gulnara Firdusovna (Journal of History Culture and Art Research, 2017)
Our paper presents a research in cognitive linguistics and considers implicit negation dialogue utterances. Implicitness exists in all natural languages and can be considered as one of the most important features in the verbal communication process. It is well known that utterances in dialogues have a high degree of the implicitness which is due to the fact that the communicants share the situation, the context and the background knowledge. The paper considers some common ways of expressing implicit negation in the dialogue utterances. The main results of the study consist in the description of the mechanism for recognizing the implicit meaning and identifying typical cases of implicit negation in dialogue utterances characterized by the asymmetry of interrogative and response replicas. The materials of the paper can contribute into the language and thinking correlation problem and be of some interest for linguists, psycho-linguists, experts in logics and philosophy.